Wildlife and wildlands: a Christian perspective - Rolston, Holmes, 1932-2025, author; Fortress Press, publisher (Colorado State University. Libraries, 1992)
The principal focus of Biblical faith is the culture established in the land. At the same time the Bible is full of constant reminders of the natural givens. Justice is to run down like waters, and the land flows with milk and honey. The fauna is included within the covenant. Life in artificial environments, without experiencing the divine creation is ungodly. Bringing a perspective of depth, Christian conviction wants sanctuaries not only for humans, but also for wildlife.
Keywords: wildlands; environmental values; endangered species; faith; land ethic; nature; landscapes; Judaism; Christianity